Participative Leadership VS Servant Leadership on Innovative Work Behavior: Role of Psychological Empowerment as Mediator - Hikmah, Khoirul; Subyantoro, Arief; Puspitaningrum, Dwi Aulia; Nasrulloh, Rifqi Syarif (Journal of Ecohumanism, 2024)
The role of psychological empowerment has not been thoroughly elucidated in previous researchers. Therefore, this study aims to examine the influence of participative and servant leadership on IWB and the role of psychological empowerment as a mediator. This study used a quantitative method with an SEM-PLS design on 155 respondents from the batik handicraft industry in Central Java, Indonesia. This finding supports the idea that participative and servant leadership, as well as psychological empowerment, are important for promoting innovation. However, psychological empowerment only strengthens the influence of servant leadership because direct participation in decision-making is already able to trigger employee initiative without the need for increased empowerment first. Servant leaders act as good mentors when organizational members experience difficulties at work, get the freedom to complete difficult tasks, are valued, trusted, and have high trust in leaders related to the principles of work ethics for the progress of the company.